Cleavage of HMGB1 by Proteolytic Enzymes Associated with Inflammatory Conditions - Sowinska, Agnieszka; Rensing, Merlin; Klevenvall, Lena; Neog, Manoj; Lundbäck, Peter; Harris, Helena Erlandsson (Frontiers in Immunology, 2020)
Extracellular HMGB1 acts as an alarmin in multiple autoimmune diseases. While its release and functions have been extensively studied, there is a substantial lack of knowledge regarding HMGB1 regulation at the site of inflammation. Herein we show that enzymes present in arthritis-affected joints process HMGB1 into smaller peptides in vitro. SDS-PAGE, western blotting and mass spectrometry analyses indicate cleavage sites for human neutrophil elastase, cathepsin G and matrix metalloproteinase 3 within the HMGB1 structure. While human neutrophil elastase and matrix metalloproteinase 3 might theoretically improve the affinity of HMGB1 to its receptors by cleaving the acidic C-terminal tail, cathepsin G completely degraded the alarmin. Contrary to a previous report we demonstrate that HMGB1 is not a substrate for dipeptidyl peptidase IV. We also provide novel information regarding the presence of these proteases in synovial fluid of juvenile idiopathic arthritis patients. Correlation analysis of protease levels and HMGB1 levels in synovial fluid samples did not, however, reveal any direct relationship between the recorded levels. To our knowledge this is the first study investigating the proteolytic processing of HMGB1 and provides insight into enzymatic regulation of HMGB1 during inflammatory disease, in this case juvenile idiopathic arthritis.